Food systems, land use change and mitigation initiatives in Caquetá, Colombia - Rodríguez, Luz A.; Maya, Diana Lucía; Gómez, Thomas; Buitrago, Juliana; Álvarez, Javier (2023)
In this document we present a general characterization of the food systems in the department of Caquetá, Colombia, based on a review of the literature, with a particular emphasis on livestock and cocoa. It is worth mentioning that, according to our findings, most of the studies have a departmental emphasis2 which highlights the importance of deepening in local studies, that provide more specific information on the functioning and features of food systems, their articulation to local, national and international value chains, as well as their potential and challenges in terms of mitigation and adaptation to climate change. Likewise, we observed a gap in the development of research that addresses differential approaches regarding gender, youth and other relevant population groups for the discussion of food systems sustainability.